Parity-time-symmetric quantum critical phenomena - Yuto Ashida (Nature Portfolio, 2017)
Parity-time (PT) symmetry has been mainly studied in optical and weakly interacting open quantum systems without many-body correlations. Here the authors show that in a strongly correlated many-body system the interplay between correlations and PT symmetry leads to the emergence of new critical phenomena.